An evaluation of behaviour change techniques in health and lifestyle mobile applications. (March 2020) - Antezana, Gaston; Venning, Anthony; Blake, Victoria; Smith, David; Winsall, Megan; Orlowski, Simone; Bidargaddi, Niranjan
Despite the current popularity and potential use of mobile applications (apps) in the area of behaviour change, health promotion, and well-being for young people, it is unclear whether their design is underpinned by theory-based behaviour change techniques. Understanding the design of these apps may improve the way they can be used to support young people's well-being.The objectives of this study were to investigate what behaviour change techniques are included in the content of health and lifestyle apps, and determine which of these are prominent in app design. Thirty of the top-listed health and lifestyle apps across three categories (physical activity, diet, and sleep) were freely downloaded from the two most popular app stores (GooglePlay™ and AppStore™). Selected apps were used by trained researchers and the features identified coded against the Behaviour Change Techniques Taxonomy 1, a systematic classification of techniques used in behaviour change interventions. It was found that 9 of the 93 behaviour change techniques listed in the Behaviour Change Techniques Taxonomy 1 were common across the chosen health and lifestyle apps. The app found to include the most behaviour change techniques had 20 (21%), while the app found to include the least had 1 behaviour change technique (1%). The most frequently used behaviour change techniques were related to goal setting and feedback. Entire categories in the Behaviour Change Techniques Taxonomy 1 were absent in the design of the selected apps.